1990
DOI: 10.1139/t90-079
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling debris avalanche initiation

Abstract: Heavy rainfall during a January 1983 storm triggered numerous debris avalanches and associated debris torrents in the Smith Creek basin, western Whatcom County, Washington, United States. Four classes of debris avalanches are recognized: wedges, drainage depressions, logging roads, and discontinuity surfaces. Nine different debris avalanche headscarps that are representative of these four classes are studied in detail. The geometric configuration of each headscarp, the properties of soils comprising the headsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…After the fi re, Equation 6 predicts a rapid decline in C r to a minimum value close to 0·5 kPa, followed by a more gradual recovery towards pre-disturbance values ( Figure 16). Our cohesion value of 1·9 kPa is similar to previous estimates of reach-average root cohesion made using this model for similar types of streams (Eaton, 2006;Eaton and Church, 2007), and similar to hillslope-average root cohesions for similar vegetation densities estimated using pore-pressure slope failure models (Buchanan and Savigny, 1990). As a point of reference, Eaton (2006) showed that the channels studied by Hey and Thorne (1986) were associated with reachaverage C r values ranging from 1·0 kPa for weakly vegetated channels to 3·0 kPa for densely forested channels, while Eaton and Church (2007) showed that the downstream hydraulic geometries of several gravel bed streams in the continental United States were consistent with C r values ranging from 1·7 kPa to 3·0 kPa.…”
Section: R(t) + D(t)]supporting
confidence: 87%
“…After the fi re, Equation 6 predicts a rapid decline in C r to a minimum value close to 0·5 kPa, followed by a more gradual recovery towards pre-disturbance values ( Figure 16). Our cohesion value of 1·9 kPa is similar to previous estimates of reach-average root cohesion made using this model for similar types of streams (Eaton, 2006;Eaton and Church, 2007), and similar to hillslope-average root cohesions for similar vegetation densities estimated using pore-pressure slope failure models (Buchanan and Savigny, 1990). As a point of reference, Eaton (2006) showed that the channels studied by Hey and Thorne (1986) were associated with reachaverage C r values ranging from 1·0 kPa for weakly vegetated channels to 3·0 kPa for densely forested channels, while Eaton and Church (2007) showed that the downstream hydraulic geometries of several gravel bed streams in the continental United States were consistent with C r values ranging from 1·7 kPa to 3·0 kPa.…”
Section: R(t) + D(t)]supporting
confidence: 87%
“…This paradigm originated from investigations that revealed root density and strength declines following logging (Burroughs and Thomas, 1977;Ziemer, 1981). Confirmatory evidence includes field observations that total root biomass and strength are less in failed slopes than in unfailed slopes (Wu et al, 1979;Buchanan and Savigny, 1990;Schmidt et al, 2001), and controlled experiments that have found strength of soil in direct shear increases with rooting density Dakessian, 1981, 1982;Wu et al, 1988).…”
Section: Introductionmentioning
confidence: 89%
“…There are numerous other proposals to identify typical topographic features of debris flow initiation locations, e.g., Buchanan and Savigny (1990), Fannin and Rollenson (1993), Johnson and Sitar (1990), Costa (1984), Johnson and Rahn (1970), Takahashi (1980) or Statham (1976). All of these studies observe different features in the topography of debris flow initiation sites.…”
Section: Topographymentioning
confidence: 99%